Lessons learnt from the implementation of new care models in the NHS: a qualitative study of the North East Vanguards programme - David J Hunter; Gregory Maniatopoulos; Jonathan Erskine; Bob Hudson (BMJ Open)
Objective To examine lessons learnt from the implementation of five Vanguard initiatives in the North East of England.Design Data collection comprised semistructured interviews with key informants at each site.Setting The study took place across six local authority areas in the North East of England and within six clinical commissioning groups responsible for the delivery of each Vanguard’s aims and objectives.Participants Sixty-six interviewees with participants from five Vanguard initiatives in the North East of England, including senior clinicians, project leads and directors, commissioners, and healthcare managers.Results While the context for each Vanguard is separate and distinct, there also exists a set of common issues which have a regional dimension. Participants felt that the national programme helped to raise the profile of local change initiatives and also contributed to the wider understanding of regional service integration issues. At the same time our findings demonstrate that all five sites experienced, and were subject to, unrealistic pressure placed on them to deliver outcomes. Of particular concern among all sites was the sheer scale and pace of change occurring at the same time as the National Health Service was being tasked with making significant, if unrealistic, efficiency savings.Conclusions It is too early to conclude with any confidence that a successful outcome for the new care models programme will be forthcoming. While early indications show some encouraging signs of promise, the overall context in which the complex and ambitious changes are being implemented remains both fragile and fluid.